NUEVAS OBSERVACIONES SOBRE LA INHIBITION MOTORA CORTICAL Y SU POSIBLE MECANISMO COLINERGICO - OBRADOR ALCALDE, S; ARAICO REMUS, J (Instituto de Estudios Médicos y Biológicos, CD MEXICO, DF, MEX, 1945)
Following admn of various substances to the epileptic the authors conclude that those which favor the synthesis in vitro of acetylcholine by nervous tissue, as prostig-mine, vit E, cysteine, and glutamic acid, do not clearly modify the electrical cortic
BOL INST ESTUD MED BIOL
Keywords: OBSERVACIONES, INHIBITION, MOTORA, CORTICAL, MECANISMO, COLINERGICO; CIENCIAS MEDICAS; FARMACOLOGIA